Comparative assessment of the changing pattern of land cover along the Southwestern coast of Nigeria using GIS and remote sensing techniques (2022)
The changing pattern of land cover is increasingly becoming of global concern in the sustainable management of environmental resources. Different facets of the natural ecosystem continue witnessing devastation orchestrated by rapid population growth and urban expansion in the face of climate change. This study examined the contribution of human’s to the global environmental change by assessing the dynamics of land cover between 1984 and 2017 while predicting the future extent of land cover pattern for 2047 at the Epe and Igbokoda areas on the coast of southwestern Nigeria. Landsat Thematic Mapper (TM), Enhanced Thematic Mapper Plus (ETM + ), and Operational Land Imager (OLI) imageries of 1984, 2002, and 2017 respectively were acquired from the USGS to analyse the land cover changes. Supervised classification was done using the maximum likelihood classifier of Terrset version 18.31. The Change Demand Modelling of Land Change Modeller (LCM) in Terrset integrates the Markov chain for future predictions for 2047. The Epe area which typifies a rapidly urbanizing coastal environment recorded an 84.6% increase in built-up area extent between 1984 and 2017, while the built-up area of the Igbokoda area increased by 103.8% for the same period. This increment corresponds to a decrease in the spatial extent of the forested wetlands with an increase in water bodies. Expansion of water body extents indicates the interaction between the elements of climate change such as incessant flooding and anthropogenic activities like deforestation, urban expansion through sand mining and dredging. Future prediction into 2047 connotes further worsening of the situation. Therefore, solution-based sustainable coastal management practices are recommended to salvage the impoverishing coastal ecosystems from further impairment.